Conducting Product Innovation by Using Social Media among Japanese Firms - Hiroki Idota; Sheikh Abu Taher; Teruyuki Bunno; Masatsugu Tsuji (STI Policy and Management Journal, 2019)
Social media have been spreading throughout the world, and a large number of firms recognize social media as new communication tools for obtaining information on new product development. In spite of the increasing use of social media in reality, academic research on whether or how the use of social media contributes to the promotion of product innovation is as yet insufficient. This study attempts to conduct an empirical analysis of how social media use promotes product innovation in Japanese firms by collaboration with consumers based on survey data from Japanese firms using probit analysis. This study finds that collaboration with consumers by using social media is important for innovation, particularly in developing concepts and devising methods of use. Innovative firms evaluate social media as importance for the relationship of trust with consumers and recognize word-of-mouth via social media to discover new ideas, and elaborate organizational management through the person in charge of development. Social media thus play an important role in product innovation in such a way that social media support firms by aiding to grasp consumer needs and collaborate with consumers for product innovation.  Keywords: social media, product innovation, probit analysis, collaboration with consumers, business activities.